Association between Novel Marker (Platelet-Lymphocyte Ratio, Neutrophil-Lymphocyte Ratio, and Delta Neutrophil Index) and Outcomes in Sudden Cardiac Arrest Patients. (24th March 2021) - Han, Sang Il; Cha, Kyoung-Chul; Roh, Young Il; Hwang, Sung Oh; Jung, Woo Jin; Kim, Tae Youn
Abstract : Purpose . It is important that clinicians accurately predict the outcome of patients with sudden cardiac arrest (SCA). The complete blood count (CBC) is an easy and inexpensive test that provides information on blood content. Platelet-lymphocyte ratio (PLR), neutrophil-lymphocyte ratio (NLR), and delta neutrophil index (DNI) are relatively novel biomarkers that have been used in the prognosis of various diseases. We aimed to determine the usefulness of PLR, NLR, and DNI in predicting the outcomes of SCA. Materials and Methods . This retrospective observational study was performed on patients with SCA. Patients who visited the tertiary university hospital from January 2015 to December 2019 were targeted. The inclusion criteria were all nontraumatic adult out-hospital cardiac arrest patients. We analyzed DNI, PLR, and NLR based on the CBC results of all enrolled patients. The exclusion criteria were as follows: no data on laboratory study, traumatic arrest, age < 18 years, and a history of leukemia, myelodysplastic syndrome, and myelofibrosis. The primary outcome was assessed as return of spontaneous circulation (ROSC), the secondary outcome as survival to discharge, and the tertiary outcome as neurological outcome. Results . From January 1, 2015, to December 31, 2019, 739 patients were enrolled. ROSC was seen in 324 patients, of whom 60 had survival to discharge and 24 had good neurological outcome at the time of discharge (cerebral performance categories (CPCs) 1-2). The PLR of the ROSC group was 42.41 (range: 4.21–508.7), which was higher than that of the No-ROSC group (p = 0.006 ). The DNI value of the survival group was 0.00 (range: 0.00–40.9), which was lower than that of the nonsurvival group. Conclusions . Patients with SCA and subsequent ROSC had higher PLR and NLR, while those with survival to discharge had lower DNI values than those with nonsurvival to discharge (p = 0.005 ).